PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA KOPERASI KARYAWAN PT ASTON INTI MAKMUR JAKARTA SELATAN - Safatillah Fazar; Rini Septiowati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of workload and physical work environment on employee performance, both partially and simultaneously. The method used is a quantitative approach by utilizing survey methods to collect data from the population or samples in the company. The sample uses saturated sampling, so all employees are sampled in this study. The analysis method in data processing is validity and reliability testing, classical assumption testing, simple linear regression, multiple linear regression, correlation coefficient testing, determination coefficient testing, hypothesis testing (f test and t test) using SPSS version 26. The results of this study indicate that the workload value t count (1.464 <1.664). This is also strengthened by the ρ value > Sig. 0.05 or (0.147 > 0.05). Thus, H0 is accepted, this indicates that there is no significant influence partially between workload and employee performance. The value of the physical work environment t count (6.419>1.664). This is strengthened by the ρ value < Sig. 0.05 or (0.00<0.05). Thus, H2 is accepted, this indicates that there is a partial significant influence between the physical work environment and employee performance. For the simultaneous test, F count = (74.206>2.33) is obtained, this is also strengthened by the ρ value <Sig. 0.05 or (0.00<0.05). This indicates that there is a simultaneous significant influence between workload and physical work environment on employee performance.